Agreement Between a Food Frequency Questionnaire and the Willett Questionnaire in Overweight or Obese Pregnant Women - Sui, Zhixian; Moran, Lisa J; Chapple, Lee-anne; Dodd, Jodie M. (Journal of Nutritional Therapeutics, 2013)
Background & Aims: Overweight and obesity during pregnancy is associated with an increased risk of many adverse health outcomes for both women and their infants. There is a need for simple food frequency questionnaires to assess nutritional intake and aid implementation and evaluation of nutritional interventions in these women. The aim of this study was to compare a newly developed food frequency questionnaire with the Willett food frequency questionnaire in Australian pregnant women who were overweight or obese. Methods: 170 overweight or obese pregnant women (12-20 weeks’ gestation) completed both the Willett and the devised (LIMIT) food frequency questionnaire with n=41 excluded due to unrealistic energy intake or incomplete questionnaires. The mean nutrient intake for each questionnaire and the mean difference in nutrient intake between the questionnaires was assessed. The correlation and agreement between the two questionnaires were assessed by Spearmans correlation coefficients and Bland-Altman method. Results: There were high correlations for total energy intake, protein, carbohydrates, cholesterol, iron, folate, and caffeine (r>0.50, P<0.01), and moderate correlations for fat, fibre, and calcium (r=0.4-0.5, P<0.01). Correlations were low (r<0.3) for vitamins. There was no significant systematic error between the two food frequency questionnaires with the exception of alcohol, calcium, iron, and folate (P>0.05). The limit of agreement (LOA) was wide (LOA <50% or >200%) for macronutrients, calcium, and folate, but within the acceptable range for iron, vitamins, and caffeine (LOA 133%). Conclusions: There is good agreement between the Willett and the LIMIT food frequency questionnaires in estimating macronutrient and some key pregnancy-related micronutrients for group-level comparisons.